Estimating Inclusiveness of Growth in Sub-Sahara African Countries: a VAR Approach - Kehinde Kabir Agbatogun; Sunday Idowu Oladeji; Adewale Abiodun Adegboye (Universitas Negeri Malang, 2022)
The study examined the interaction among income inequality, economic growth, and poverty with a view of assessing the extent of inclusiveness of growth in selected African countries. Using a dataset from World Development Indicators (WDI) and Standardized World Income Inequality Dataset (SWIID), the study adopted Vector AutoRegression (VAR) method in its econometric analysis. Its findings show that only